Computer program design on precast prestressed hollow slab / Mohd Zamri Abdullah - Abdullah, Mohd Zamri (1997)
In designing PHCS ( Precast hollow core slab ) using manually if will take more time, cost and others constraints. Therefore, the aim of this project is to develop a computer programme for analyse, design and choose the best size using PHCS and it is also friendly used. It will be easier for the consultant engineers, architects, Quantity Survey (Q.S) and those interested to used to used the programme. The language programme going to be used is MS-DOS Q Basic. This is because is simpler and easier to used compare to any other computer language. This programme is mainly for PHCS with simply supported and cantilever slab. Which are subjected to dead load, imposed load and line load. The main constraint is that the PHCS is designed only for one - way spanning simply supported only. This is because the ratio of ly/lx > 2 (According to BS 8110 : Part 1: Clause 3.5.3). where ly the longest span and lx the shorter span. The supported condition are fixed supported, pinned supports and roller. The main finding will be to determine the maximum span of PHCS that the slab can catered which are satisfied for bending, shear and deflection. This also to design the PHCS according to the client need. Another finding is to find the suitable size of PHCS subjected to the loading being by the client.